Prognostic relevance of a non‐invasive evaluation of right ventricular function and pulmonary artery pressure in patients with chronic heart failure. (April 2013) - Ghio, Stefano; Temporelli, Pier Luigi; Klersy, Catherine; Simioniuc, Anca; Girardi, Bruna; Scelsi, Laura; Rossi, Andrea; Cicoira, Mariantonietta; Genta, Franco Tarro; Dini, Frank L.
<x xml:space="preserve">Abstract</x> Aim To determine the prognostic relevance of the echocardiographic evaluation of pulmonary artery systolic pressure (PASP) and tricuspid annular plane systolic excursion (TAPSE) in patients with chronic heart failure (CHF). Pulmonary hypertension (PH) and right ventricular (RV) dysfunction have both been associated with poor prognosis in CHF. Methods and results A complete echocardiographic examination was performed in 658 outpatients with CHF and LVEF <45%. PASP was available in 544 (83%) patients, TAPSE in all patients, and E wave deceleration time (DT) in 643 (98%) patients. During a median follow‐up period of 38 months, 125 patients died, 5 underwent urgent heart transplantation, and 5 had an appropriately detected and treated episode of ventricular fibrillation. At Cox survival analysis (composite endpoint was death, urgent heart transplantation, and ventricular fibrillation), patients with PASP ≥40 mmHg plus TAPSE ≤14 mm had a poorer prognosis than those with high PASP but preserved TAPSE; RV dysfunction associated with normal PASP did not carry additional risks. Similar results were obtained when patients were grouped on the basis of DT (restrictive vs. non restrictive) and TAPSE. Conclusions A simple echocardiographic evaluation of PASP and RV function with TAPSE may improve risk stratification in patients with CHF. Importantly, if PASP cannot be recorded at echocardiography, a restrictive DT, measurable in the vast majority of patients, may be coupled with TAPSE to stratify patients.